Characterization and Conservation of Native Banana Germplasms Available in Salt Ecosystem: Conservation and Characterization of Native Banana Germplasms (Journal of the Bangladesh Agricultural University, 2024)
This study aimed to assess, conserve, and characterize banana germplasms in Bangladesh's coastal salt ecosystem, with the goal of improving cultivation resilience and sustainability under challenging environmental conditions. Thirty-five banana germplasms were subjected to in situ investigation, with 11 germplasms undergoing morphological characterization, revealing significant variations in key parameters. Additionally, 11 germplasms representing Musa species were collected for ex situ conservation at the Germplasm Center, Department of Horticulture, PSTU, with three, four, and four germplasms falling under Musa paradisiaca, Musa acuminata, and Musa sapientum, respectively. Notably, M. paradisiaca (kacha kola), M. acuminata (atia kola), and M. sapientum (table banana) exhibited promising traits in terms of morphological characteristics, total yield, and shelf-life. Among these, germplasm MP01 (M. paradisiaca), MA17 (M. acuminata), and MS09 (M. sapientum) demonstrated superior potential for maximizing production and profitability within the coastal salt ecosystem region. These findings offer valuable insights for banana cultivation in similar challenging environments, contributing to enhanced agricultural sustainability and livelihoods.J Bangladesh Agril Univ 22(2):193-201,2024